"In vitro" medium term preservation of different romanian landraces - Botau, Dorica; Danci, Marcel; Danci, Oana (Acta Biologica Szegediensis, 2005)
In order to conserve important sources of variety as the landraces collected of four economically, alimentary and agriculturally important culture species, we developed a cheap protocol of slowing plants growth that uses in vitro cultures and low temperatures. Thus, as nutrients generator we used MS without growth regulators medium in the presence or absence of sucrose. The cultures were incubated in two growth rooms differing by temperature 16°C and 24°C, respectively. The results obtained on MS without sucrose medium and at temperatures of 16°C consisted of decreasing the regenerative capacity from 17% to 39% and slow down plants growth between 42% and 85% (see table).